Matching with contracts: an efficient marriage market? - Zeng, C (University of Oxford, 2012)
This paper studies a marriage market with two-sided information asymmetry in whichthe gains from marriage are stochastic. Contracts specify divisions of ex-post realizedmarital surplus. I first study a game in which one side of the matching market offerscontracts. I show that when expected marital surplus is strictly monotonic in agents